Comparing rural traffic safety in Canada and Australia: a scoping review of the literature - Hannah Mason; Jason Randall; Peter Leggat; Don Voaklander; Richard Franklin (James Cook University, 2022)
Introduction: The reduction of road fatalities is a priority established by the WHO and ratified by the UN. Rates of road fatalities are disproportionately high in rural areas in both Australia and Canada, two Commonwealth countries with comparable healthcare systems and rural health challenges. The purpose of this review was to compare and contrast the epidemiology, risk factors and prevention strategies of rural road fatalities in both countries to inform the next steps for prevention. Methods: A scoping literature review was undertaken systematically to search for peer-reviewed literature published from January 2000 to June 2021. Articles were reviewed from five databases (EMCARE, Medline, CINAHL, Scopus and Informit). Search terms were adapted to suit each database and included combinations of keywords such as 'traffic accident', 'fatality', 'rural/remote', 'Australia' and 'Canada'. Themes and data associated with the research outcomes were extracted and tabulated. Results: Forty-three papers were identified as relevant: 14 exploring epidemiology, 25 investigating risk factors and 37 proposing prevention strategies. People living in rural locations were 3.2 (95% confidence interval: 3.0-3.5) times more likely than urban dwellers to die in road-related incidents, with rates of motor vehicle fatalities universally higher. Common risk factors included drugs and alcohol, speed, driver error and biological sex. Key prevention strategies included improved infrastructure, vehicle design, impaired driving prevention and education. Conclusion: Further research regarding preventative measures and significant investment in rural road safety in both Australia and Canada are needed to prevent future incidents.